KEBERLANJUTAN EKONOMI LOKAL MASA PANDEMI COVID-19 - Mar’I Muhammad Hadiq (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN EKONOMI DAN HUKUM ISLAM), 2022)
The 2019 Corona Virus Disease (Covid-19) pandemic has spread throughout the region, the economic aspect is the impact that gets the most attention after the health aspect. Kapuas Hulu's economy has declined due to external influences as well as local conditions. The economic crisis must be addressed immediately so that it does not sink further into an economic depression. Therefore, the economic recovery must be immediately designed and started to be implemented. Through a qualitative descriptive study, this paper aims to reveal the economic base in Kapuas Hulu to carry out economic recovery due to the Covid-19 pandemic. Kapuas Hulu is rich in natural resources, as well as the majority of its people as farmers in a broad sense and mining, so the economic recovery strategy is to rely on the agricultural sector and people's businesses on commodities that are business-worthy, develop local trade and markets, apply information technology, and encourage micro, small and medium enterprises (MSMEs), including cooperatives, Village Owned Enterprises (BUMDes) and Regional Owned Enterprises (BUMD). As a strengthening of the recovery program, there must be policies and facilities from the government to mobilize and expedite recovery efforts, and must involve large companies in the regions to help empower the business aspects of people's businesses.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The results of this study are economic recovery in several countries by subsidizing workers' wages, encouraging the development of tourist innovations, relaxing direct loans and digitalization in developing MSMEs and optimizing tourism. While our country's economic recovery strategy can also carry out the same strategy to increase economic recovery among the strategies that can be implemented include: Providing social assistance to business actors, tax incentives, loan relaxation, providing working capital, providing product buffers, e-learning coupled with strategies long term and short term as is the handling of Covid-19.